The neurochemical changes in the innervation of human colonic mesenteric and submucosal blood vessels in Ulcerative colitis and Crohn's disease. Issue 5 (5th March 2014) - de, D.; Brookes, S. J.; Gibbins, I.; Sia, T. C.; Wattchow, D. A.
Abstract Background Neurogenic inflammation involves vasodilation, oedema and sensory nerve hypersensitivity. Extrinsic sensory nerves to the intestinal wall mediate these effects and functional subsets of these extrinsic nerves can be characterized by immunohistochemical profiles. In this study such profiles were examined in samples from patients with inflammatory bowel disease (IBD), in particular ulcerative colitis (UC) and Crohn's disease (CD). Methods Healthy margins from cancer patients were compared to specimens from IBD patients. All nerve fibres were labelled by PGP 9.5. Double and triple labelling with TH, NPY, SP, SOM, NOS, VIP, VAChT, CGRP, TRPv1 were performed. Perivascular nerve fibres in the mesentery, and submucosa, were examined. The percentage of all labelled nerve fibres was calculated with a transect method. Key Results Total number of varicosities on mesenteric vessels increased in IBD but decreased around submucosal vessels. The percentage of nerve fibres around submucosal arteries labelled by SP increased from 11% in controls to 20% (UC) and 24% (CD) and mesenteric artery nerve fibres were unchanged. Nerve fibres labelled by SOM were markedly reduced surrounding submucosal arteries, from 22% to 1% (UC) and 2% (CD), but not perivascular mesenteric nerve fibres. 87 to 93% of SP immunoreactive nerve fibres were also reactive for TRvP1. TRPv1 labelling without SP was 12%in controls and increased to 40% in CD submucosal specimens. Conclusions & Inferences There is an increase in SP and TRPv1, and a reduction in SOM immunoreactive nerve fibres in IBD. Changes in the perivascular functional nerve subclasses may underlie the hyperaemia, and ulceration, characteristic of IBD. Furthermore, pain may relate to underlying neural changes.